Evolution of ligands, receptors and metabolizing enzymes of thyroid signaling. (25th December 2017) - Holzer, Guillaume; Roux, Natacha; Laudet, Vincent
Abstract: Thyroid hormones (THs) play important roles in vertebrates such as the control of the metabolism, development and seasonality. Given the pleiotropic effects of thyroid disorders (developmental delay, mood disorder, tachycardia, etc ), THs signaling is highly investigated, specially using mammalian models. In addition, the critical role of TH in controlling frog metamorphosis has led to the use of Xenopus as another prominent model to study THs action. Nevertheless, animals regarded as non-model species can also improve our understanding of THs signaling. For instance, studies in amphioxus highlighted the role of Triac as a bona fide thyroid hormone receptor (TR) ligand. In this review, we discuss our current understanding of the THs signaling in the different taxa forming the metazoans (multicellular animals) group. We mainly focus on three actors of the THs signaling: the ligand, the receptor and the deiodinases, enzymes playing a critical role in THs metabolism. By doing so, we also pinpoint many key questions that remain unanswered. How can THs accelerate metamorphosis in tunicates and echinoderms while their TRs have not been yet demonstrated as functional THs receptors in these species? Do THs have a biological effect in insects and cnidarians even though they do not have any TR? What is the basic function of THs in invertebrate protostomia? These questions can appear disconnected from pharmacological issues and human applications, but the investigation of THs signaling at the metazoans scale can greatly improve our understanding of this major endocrinological pathway. Highlights: The biological role of non-canonical ligands remains to be explored in vertebrates. Comparative endocrinology shows that T4 and T3 might not be the original TR ligands. The role of non-canonical ligands remains to be understood outside vertebrates.